Area Baltera: Riva del Garda (Trento) - Heliopolis 21 (AND Rivista di architetture, città e architetti, 2020)
The intervention is strategically placed in the existing context and merges with the pre-existing ones thanks to a unitary distribution system, carrying out an intervention of requalification and environmental enhancement of a purely industrial area called Baltera.